Streamings de vídeo com uso do powerpoint como metodologia de ensino de eletricidade para turmas do ensino médio - Almeida, Antônio Eleison Pinheiro de (2023)
With objective of presenting a simple work and with a good alternative to the use of news technologies, this dissertation is used on how to obtain a good Electricity learning, using as a new teaching technology, the use of videos streaming. The usefulness of this dissertation is relevant for the teachers who intend to teach electricity classes to 3rd year high school students. The research related to the work was done with the students as the author of this dissertation teach physics classes. The classes used in this research were the classes formed by students of the 3rd year of high school, which the author of this dissertation teaches classes in regular high school in the city of Fortaleza, state of Ceará. As will be started later, despite the simple proposal, it has good teaching potential if the teacher is didactically together with the student. Multicast video streaming was used, that is video streaming and the interaction between student and teacher is great. Specifying are Google Meet type video streaming. It will be important to master the content by the teacher who will apply the educational product of my dissertation, as well as the didactic follow-up of the teacher with his students. This will be necessary to succeed in teaching electricity through video streaming.